The correlation between thoracic radiographic findings in pulmonary tuberculosis and type 2 diabetes mellitus - Pinem, Della Terulin; Nasution, Ikhwanul Hakim; Pulungan, Ica Yulianti (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2025)
Tuberculosis (TB), specifically pulmonary tuberculosis, is a contagious chronic infectious disease caused by Mycobacterium tuberculosis. Type 2 diabetes mellitus (T2DM) is a significant comorbidity that influences the clinical presentation of TB. Patients with pulmonary TB and T2DM exhibit a more severe clinical profile and a broader range of symptoms compared to those with PTB alone. Radiologically, TB-T2DM patients often present with more extensive, multilobular lesions and a higher incidence of cavitation. This study aimed to determine the association between the characteristics of chest X-ray findings in patients with pulmonary TB complicated by T2DM and those without T2DM at Royal Prima General Hospital, Medan. This research employed a quantitative methodology with a cross-sectional design. The sample comprised 50 medical records of pulmonary TB patients with T2DM and 50 medical records of pulmonary TB patients without T2DM. Data analysis involved univariate and bivariate statistical methods. The results indicated that the extent of lesions observed on chest X-rays in patients with pulmonary TB patients with T2DM, as well as those without T2DM, varied from minimal to moderate to extensive. The types of lesions identified included infiltrates, infiltrates with fibrosis, and fibrosis. No significant association was found between the extent of lesions or the type of lesions in pulmonary TB patients with T2DM and those without T2DM. The most prevalent lesion extent was moderate, and the most common lesion type was infiltrates with fibrosis.